Formation of superparamagnetic nanoclusters in Fe implanted Al2O3 - Bharuth-Ram, K.; Doyle, T. B.; Adoons, Vanthini Nelson; Moodley, M. K.; Ronning, Carsten (Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms, 2017)
Conversion electron Mössbauer spectroscopy (CEMS) measurements have been performed on single crystal Al2O3 implanted with 56Fe and 57Fe ions to a total fluence of 1.2 × 1016/cm2, corresponding to a concentration of approx. 4 at.%. The CEM spectrum in the ‘as-implanted’ state is in good agreement with earlier studies. Annealing at temperatures above 600 °C resulted in significant changes, with the spectra after the annealing at TA ≥ 800 °C displaying paramagnetic doublets characteristic of superparamagnetic nanoclusters. Magnetization curves of the annealed sample show hysteresis loops with zero coercive field while the analysis of low temperature magnetic isotherms in terms of the Langevin function for superparamagnetic particles yields an average radius of 2–3 nm for the Fe clusters.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Al; CEMS; Fe implantation; Nanoclusters; VSM